Odpowiedzi

2010-01-24T13:43:16+01:00
A] a+(a-b)= a+a-b = 2a-b
b] 2x-(x-4)= 2x-x+4 = x+4
c] 7-(-x+6)= 7+x-6 = x+1
d] -(x+4)+(x-5)= -x-4+x-5 = -9
e] 1-(t+p)-(t-2)= 1-t-p-t+2 = -2t-p+3
f] -(-y+2)+(-2y-4)= y-2-2y-4 = -y-6
2010-01-24T13:44:03+01:00
A] a+(a-b)= 2a-b
b] 2x-(x-4)= x+4
c] 7-(-x+6)= x+1
d] -(x+4)+(x-5)= -9
e] 1-(t+p)-(t-2)= 3-2t-p
f] -(-y+2)+(-2y-4)= -y-6
2010-01-24T14:15:22+01:00
1. a+(a-b)= a +a-b = 2a-b
2. 2x-(x-4)= 2x- x+4 = x+4
3. 7-(-x+6)= 7 +x-6 = x+1
4. -(x+4)+(x-5)= -x-4 +x-5 = -9
5. 1-(t+p)-(t-2)= 1-t-p-t+2 = -2t-p+3
6. -(-y+2) + (-2y-4)= y- 2-2y -4 = -y -6